1983
DOI: 10.1063/1.94383
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution of thermal wave microscopes

Abstract: It is demonstrated theoretically and confirmed experimentally that the intrinsic spatial resolution of a thermal wave microscope in the extreme near field limit is independent of thermal wavelength and is determined by the depth of the thermal scatterer beneath the surface of the specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In one of these experiments [13] the scatterer has a continuously varying aepth. In this experiment the observed resolution is two or three oraers of magnitude better than the acoustic wavelength and deteriorates linearly with depth, as predicted by the extreme-near-field theory [12]. Another recent experiment using such a microscope has been carried out on an aluminum bicrystal having a nearly vertical grain boundary [15].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In one of these experiments [13] the scatterer has a continuously varying aepth. In this experiment the observed resolution is two or three oraers of magnitude better than the acoustic wavelength and deteriorates linearly with depth, as predicted by the extreme-near-field theory [12]. Another recent experiment using such a microscope has been carried out on an aluminum bicrystal having a nearly vertical grain boundary [15].…”
Section: Discussionmentioning
confidence: 88%
“…The inverse power of the distance which appears in the Green's function is assumed to De slowly varying in both of these limits. However, in the situation which we described aoove, with a small source which can be brought close to the scatterer, the variation of the phase factor is dominated by that of the inverse power of the distance, and the scattering becomes quasi-static (extreme-near-field 1 imit) [12]. In this limit the incident energy is effectively localized to a region of the scatterer whose dimensions are comparable to the size of the source or the source-scatterer distance, whichever is larger.…”
Section: Discussionmentioning
confidence: 99%
“…By operat ing in a differentia1 mode one may map spectroscopic absorption differences in the ne ar fie1d 1i mit [20], thereby obtaining resolution greater than either the therma1 or IR wave1engths emp10yed. By scanning the samp1e stage, a map of absorption may be made at a number of wave1engths.…”
Section: Spectroscopic Mapping Of Organic Filmsmentioning
confidence: 99%
“…If we assume a Gaussian shaped optical pulse of duration r, and intensity 1, the source term in Eq. (3) becomes 2 P(z,t) = I(l_R)aRe-az e-(t/r) (4) where R and a are the metal reflectivity and absorbtivity, respectively. Substituting this heating source term into Eq.…”
Section: Tbermal Transport: Time Domainmentioning
confidence: 99%
“…This technique uses short laser pulses to heat the sample surface, followed by a timeresolved measurement of the black-body radiat ion to determine the surface cooling rate. Another method, photothermal deflectometry, has been used to determine thermal properties by measuring the optically-induced thermoelastic deformation of the surface or the heating induced refractive index gradient in a gas above the surface [3,4]. More recently, Rosencwaig et al [5] have shown that a modulated thermoreflectance measurement is an equally sensitive method which can yield the same informat ion as the deflection techniques.…”
mentioning
confidence: 99%